Holistic nursing care practice and associated factors among nurses in public hospitals of Wolaita zone, South Ethiopia - Selamawit Ataro Ambushe; Nefsu Awoke; Birhanu Wondimeneh Demissie; Tiwabwork Tekalign (BMC, 2023)
Abstract Background Holistic nursing care is an approach to patient care that takes into account the physical, social, spiritual, and psychological needs of the patient. Providing holistic care has been found to be an effective way to prevent diseases and death, as well as improve the quality of healthcare provided to patients. However, despite its perceived benefits, many nurses lack experience with holistic care and only focus on patients' physical needs, treating them as biological machines while ignoring their spiritual, mental, and social needs. Therefore, this study aimed to assess the practice of holistic nursing care and its associated factors among nurses. Methods A hospital-based cross-sectional study was conducted among 422 sampled Nurses working in public hospitals in Wolaita Zone. Systematic random sampling was applied to select the study participants. A self-administered, pretested questionnaire was used to collect the data. The collected data were entered into Epi Data version 4.6 and analyzed using SPSS version 25. Binary and multivariable logistic regression analyses were used to identify factors associated with holistic nursing care practice. Statistical significance was declared at a p-value less than 0.05. The strength of the association was indicated by the AOR and 95% CI. Result The study found that the overall practice of holistic nursing care was 21%. Nurses with a diploma in nursing (AOR: 0.28; 95% CI: 0.11, 0.71), nurses working in a hospital with no continuous in-service learning (AOR: 0.39; 95% CI: 0.20, 0.76), nurses with a poor relationship with patients (AOR: 0.31; 95% CI: 0.16, 0.58), and nurses with poor knowledge of holistic nursing care practice (AOR: 0.41; 95% CI: 0.21, 0.7) were factors associated with a lower likelihood of practicing holistic nursing care. Conclusion This study found that the practice of holistic nursing care among nurses working in public hospitals in the Wolaita Zone was low. Level of education, the unit of work, continuous in-service learning, the nurse-patient relationship, and the knowledge of nurses were factors associated with holistic nursing care. The provision of in-service training and the creation of trusting, positive relationships were suggested to improve the practice of holistic nursing care.